Teach Aquaculture Curriculum: What Makes a Good Fish Food? - Craig S. Kasper; Cortney L. Ohs; Brian E. Myers; Frank A. Chapman; Amber L. Garr; R. Leroy Creswell; Carlos V. Martinez; Elisa J. Livengood (EDIS, 2010)
FA172, a 5-page activity by Craig S. Kasper, Cortney L. Ohs, Brian E. Myers, Frank A. Chapman, Amber L. Garr, R. Leroy Creswell, Carlos V. Martinez, and Elisa J. Livengood, is activity 22 of the Teach Aquaculture Curriculum. In this activity for grades 9-12, students will learn the common ingredients in fish food, design their own fish food, and discover how water stability relates to fish nutrition, production, and the environment. Includes student performance standards. Published by the UF School of Forest Resources and Conservation, Program in Fisheries and Aquatic Sciences, July 2010.